THE EFFECT OF ABS MOBILE SERVICE QUALITY ON THE LOYALTY OF MEMBERS OF KSPPS ARTHA BAHANA PATI - Umini Umini; Puji Lestari (NUsantara Islamic Economic Journal, 2022)
This study, entitled The Effect of ABS Mobile Service Quality on Loyalty of KSPPS Artha Bahana Pati, aims to examine whether there is an effect of ABS Mobile Service Quality on Member Loyalty at KSPPS Artha Bahana Pati. This research is a descriptive quantitative research. In conducting this research, the method used is the survey method, namely research that takes a sample from a population and uses a questionnaire as the main data collection tool, the data used is primary data obtained from distributing questionnaires, namely the KSPPS Artha Bahana members. ABS Mobile. The results of this study indicate that, in terms of the five indicators used as a reference in assessing the quality of ABS Mobile services (Tangible, Reliability, Empathy, Responsiveness, and Assurance) there is a significant positive influence between the quality of ABS Mobile services on the loyalty of members of KSPPS Artha Bahana Pati, which is proven from the F test of 5,589 is greater than the F table, namely 2.31 (F count 5,589 ˃ F table 2.31). Supported again with a significant level of 0.00 <0.05, less than 0.05, which indicates that the quality of ABS Mobile services has a significant effect on Member Loyalty. The results of the R2 test are 0.188 (18.8%). This means that the quality of ABS Mobile services has an effect of 18.8% on the loyalty of KSPPS Artha Bahana Pati members.